Factors Associated with Time to Conversion from Active Surveillance to Treatment for Prostate Cancer in a Multi-Institutional Cohort. Issue 5 (10th November 2021) - Cooley, Lauren Folgosa; Emeka, Adaeze A.; Meyers, Travis J.; Cooper, Phillip R.; Lin, Daniel W.; Finelli, Antonio; Eastham, James A.; Logothetis, Christopher J.; Marks, Leonard S.; Vesprini, Danny; Goldenberg, S. Larry; Higano, Celestia S.; et al.
Abstract : Abstract : Purpose: We examined the demographic and clinicopathological parameters associated with the time to convert from active surveillance to treatment among men with prostate cancer. Materials and Methods: A multi-institutional cohort of 7, 279 patients managed with active surveillance had data and biospecimens collected for germline genetic analyses. Results: Of 6, 775 men included in the analysis, 2, 260 (33.4%) converted to treatment at a median followup of 6.7 years. Earlier conversion was associated with higher Gleason grade groups (GG2 vs GG1 adjusted hazard ratio [aHR] 1.57, 95% CI 1.36–1.82; ≥GG3 vs GG1 aHR 1.77, 95% CI 1.29–2.43), serum prostate specific antigen concentrations (aHR per 5 ng/ml increment 1.18, 95% CI 1.11–1.25), tumor stages (cT2 vs cT1 aHR 1.58, 95% CI 1.41–1.77; ≥cT3 vs cT1 aHR 4.36, 95% CI 3.19–5.96) and number of cancerous biopsy cores (3 vs 1–2 cores aHR 1.59, 95% CI 1.37–1.84; ≥4 vs 1–2 cores aHR 3.29, 95% CI 2.94–3.69), and younger age (age continuous per 5-year increase aHR 0.96, 95% CI 0.93–0.99). Patients with high-volume GG1 tumors had a shorter interval to conversion than those with low-volume GG1 tumors and behaved like the higher-risk patients. We found no significant association between the time to conversion and self-reported race or genetic ancestry. Conclusions: A shorter time to conversion from active surveillance to treatment was associated with higher-risk clinicopathological tumor features. Furthermore, patients with high-volume GG1 tumors behaved similarly to those with intermediate and high-risk tumors. An exploratory analysis of self-reported race and genetic ancestry revealed no association with the time to conversion.